Revealing Grain Boundaries and Defect Formation in Nanocrystal Superlattices by Nanodiffraction. Issue 50 (14th November 2019) - Mukharamova, Nastasia; Lapkin, Dmitry; Zaluzhnyy, Ivan A.; André, Alexander; Lazarev, Sergey; Kim, Young Yong; Sprung, Michael; Kurta, Ruslan P.; Schreiber, Frank; Vartanyants, Ivan A.; Scheele, Marcus
Abstract: X‐ray nanodiffraction is applied to study the formation and correlation of domain boundaries in mesocrystalline superlattices of PbS nanocrystals with face‐centered cubic structure. Each domain of the superlattice can be described with one of two mesocrystalline polymorphs with different orientational orders. Close to a grain boundary, the lattice constant decreases and the superlattice undergoes an out‐of‐plane rotation, while the orientation of the nanocrystals with respect to the superlattice remains unchanged. These findings are explained with the release of stress on the expense of specific nanocrystal–substrate interactions. The fact that correlations between adjacent nanocrystals are found to survive the structural changes at most grain boundaries implies that the key to nanocrystal superlattices with macroscopic domain sizes are strengthened interactions with the substrate. Abstract : Nanofocused X‐ray scattering is applied to resolve the mesocystalline structure of PbS nanocrystal superlattices and investigate structural changes near grain boundaries. Two polymorphs are identified, which only differ in terms of the orientation of the nanocrystals to the superlattice. Between two single‐crystalline domains, the superlattice contracts and undergoes an out‐of‐plane rotation, which may play an important role in defect formation.